A linkage map of 10 loci flanking the Marfan syndrome locus on 15q: results of an International Consortium study. Issue 2 (February 1992) - Sarfarazi, M; Tsipouras, P; Del Mastro, R; Kilpatrick, M; Farndon, P; Boxer, M; Bridges, A; Boileau, C; Junien, C; Hayward, C
Abstract : Members of an International Consortium for Linkage Analysis of the Marfan Syndrome (MFS1) have pooled data for joint analysis in an attempt to determine the precise location of the MFS1 gene and the order of 10 DNA markers on 15q. Five laboratories performed a total of 2111 genotypes in 22 families consisting of 225 affected and 248 normal subjects. For each marker a mean of 98 meioses was informative. D15S48 and D15S1 were identified as the closest linked markers with 99% upper confidence intervals of 12% and 13% respectively. We have used the CRI-MAP program to construct the most likely order as: D15S24-D15S25-D15S1-MFS1-D15S48-D15S49+ ++-(D15S45/S51)-(D15S29/S38). Placement of D15S2 in relation to -D15S1-D15S48- cannot be determined with certainty. The genetic map of these markers extends 53.6 cM in males and 65.0 cM in females with a sex averaged map of 60.7 cM. The sex difference was statistically significant (p = 0.005). Linkage heterogeneity between 22 MFS1 families was documented (p = 0.009) necessitating the exclusion of one family from the analysis. However, comparison of the remaining 21 families for two point and multipoint lod scores showed no evidence for linkage heterogeneity of the MFS1 locus.